Development of a hybrid precast wall system for seismic resistance - Hadiwijaya, Irma Juwitasari; Pennung Warnitchai; Sun Sayamipuk; Anwar, Naveed; Kyung-Ho, Park; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
Many existing precast concrete shear walls were designed based on monolithic emulation concept. Under earthquake, this type of walls will have numerous cracks in the wall panels and large residual drift. Then in 1999, Priestley developed shear walls that built using rocking wall concept with energy dissipators, called hybrid precast walls. Rocking wall is the wall that connected to the foundation and between wall panels using unbonded Post-tensioning Tendons (PT). Then, the interfaces were casted using fiber cement grout. When lateral load is applied, this type of wall will have gaps opened when the load is applied and closed when the load is removed. The advantage is that the wall will have self centering; no damage in wall panels, but it can undergo large displacement. This concept is then developed in several countries, such as USA and New Zealand. Different type of energy dissipators and ways to reduce shear slip and spalling in wall toe were proposed. Then in this study, Buckling Restrained Braces (BRB) as energy dissipater was proposed. Steel plate also added in the wall toe region to reduce spalling in that area. To avoid shear slip, shear keys were added. At the end, the wall assemblage shows it could work perfectly until BRB fracture in early 2.50% story drift.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2009
Keywords: Precast concrete construction